Boundedness of Singular Integral Operators with Variable Kernels on Weighted Weak Hardy Spaces. (23rd January 2014) - Wang, Hua
Abstract : LetT Ω be the singular integral operator with variable kernelΩ ( x, z ) . In this paper, by using the atomic decomposition theory of weighted weak Hardy spaces, we will obtain the boundedness properties ofT Ω on these spaces, under some Dini type conditions imposed on the variable kernelΩ ( x, z ) .